Making Noise Intentional: A Study of Servo Sound Perception - Moore, Dylan; Tennent, Hamish; Martelaro, Nikolas; Ju, Wendy (2017 12th ACM/IEEE International Conference on Human-Robot Interaction (HRI, 2017)
How do sounds shape interaction with robots? The present study explores aural impressions associated with servo motors commonly used to prototype robotic motion. This exploratory analysis constructs a framework to objectively and subjectively characterize sound using acoustic analyses and novice evaluators on Amazon Mechanical Turk. Participants evaluated unfamiliar sounds through pairwise comparison, resulting in subjective ratings of servo motor sounds. In this study, subjective measures of sound correlated well internally, but correlated weakly with objective measures. Moreover, qualitative commentary offered by participants suggests both anthropomorphic associations with sounds as well as negative impressions of the sounds overall. We conclude with a roadmap for exploration into the field of consequential sonic interaction design.